Regional Government Strategy For Facing Cybercrime At Bank BSI Syariah Tanjungpinang - Sofia, Sofia; Nurlaily, Nurlaily; Shahrullah, Rina Shahriyani (Journal of Law and Policy Transformation, 2024)
This study aims to analyze the role of local government in formulating public policies for handling Cybercrime at BSI Syariah Bank in Tanjungpinang City. Cybercrime is a serious threat to the banking sector. Thus, local governments have a responsibility to protect the public and ensure security in transactions in this sector. This study uses qualitative research method using literature studies as a data source. Relevant literature sources such as journals, scientific articles, and related policy documents, are collected and analyzed qualitatively. The purpose of this study is to provide a better understanding of the role of local government in formulating effective public policies in handling cybercrime at BSI Syariah Bank in Tanjungpinang City. It is found that Bank BSI Syariah Tanjungpinang requires stronger prevention and control measures against Cybercrime. This includes increasing internal awareness, implementing appropriate security technologies, and collaborating with law enforcement authorities. Meanwhile, the Tanjungpinang City government needs to increase its role in enforcing strict policies and law enforcement against Cybercrime perpetrators, as well as strengthening cross-sector cooperation to deal with this threat effectively.